Monty Hall three door 'anomaly' revisited: a note on deferment in an extensive form game - Philipp E. Otto (Mind & Society, 2021)
The Monty Hall game is one of the most discussed decision problems, but where a convincing behavioral explanation of the systematic deviations from probability theory is still lacking. Most people not changing their initial choice, when this is beneficial under information updating, demands further explanation. Not only trust and the incentive of interestingly prolonging the game for the audience can explain this kind of behavior, but the strategic setting can be modeled more sophisticatedly. When aiming to increase the odds of winning, while Monty's incentives are unknown, then not to switch doors can be considered as the most secure strategy and avoids a sure loss when Monty's guiding aim is not to give away the prize. Understanding and modeling the Monty Hall game can be regarded as an ideal teaching example for fundamental statistic understandings.
Keywords: A29; B55; C73; 300; Three door dilemma; Sequential choices; Behavioral theory; Initial intuition; Forward induction; Trust games